From the Rising of the Sun: Theology of Mission in the Book of Malachi - Jakada, Yakubu (Perichoresis, 2025)
As the brilliant and beautiful sunlight at dawn introduces the day and its blessings, the book of Malachi introduces New Testament mission. This paper argues that from the Old Testament, Malachi introduced universal mission which began with the ministry of Christ and will continue to the end of the age. In Malachi can be found the possible origin of the concept of "mission from everywhere to everywhere." This paper surveyed the concepts of mission in the Old Testament to give a background to Malachi’s message. The missiological interpretation of Malachi 1:11 shows that God unfolded in Malachi, the purpose of mission, the focus of mission, the scope of mission, and the fruit of mission. The understanding of the missionary message of Malachi will be an encouragement to leaders and practitioners of mission to forge ahead with the Great Commission as they receive the prophetic assurance of God’s universal intention for the salvation of mankind. The study will involve a review of some literature on Old Testament concepts of mission, a missiological interpretation of Malachi 1:11, and how Malachi’s message connects New Testament and contemporary practice of missions.